Changes in the gut microbiota of patients with sarcopenia based on 16S rRNA gene sequencing: a systematic review and meta-analysis - Song, Qi; Zhu, Youkang; Liu, Xiao; Liu, Hai; Zhao, Xinyi; Xue, Liyun; Yang, Shaoying; Wang, Yujia; Liu, Xifang (Frontiers in Nutrition, 2024)
Introduction Sarcopenia, an age-related disease, has become a major public health concern, threatening muscle health and daily functioning in older adults around the world. Changes in the gut microbiota can affect skeletal muscle metabolism, but the exact association is unclear. The richness of gut microbiota refers to the number of different species in a sample, while diversity not only considers the number of species but also the evenness of their abundances. Alpha diversity is a comprehensive metric that measures both the number of different species (richness) and the evenness of their abundances, thereby providing a thorough understanding of the species composition and structure of a community. Methods This meta-analysis explored the differences in intestinal microbiota diversity and richness between populations with sarcopenia and non-sarcopenia based on 16 s rRNA gene sequencing and identified new targets for the prevention and treatment of sarcopenia. PubMed, Embase, Web of Science, and Google Scholar databases were searched for cross-sectional studies on the differences in gut microbiota between sarcopenia and non-sarcopenia published from 1995 to September 2023 scale and funnel plot analysis assessed the risk of bias, and performed a meta-analysis with State v.15. 1. Results A total of 17 randomized controlled studies were included, involving 4,307 participants aged 43 to 87 years. The alpha diversity of intestinal flora in the sarcopenia group was significantly reduced compared to the non-sarcopenia group: At the richness level, the proportion of Actinobacteria and Fusobacteria decreased, although there was no significant change in other phyla. At the genus level, the abundance of f-Ruminococcaceae; g-Faecalibacterium, g-Prevotella, Lachnoclostridium, and other genera decreased, whereas the abundance of g-Bacteroides, Parabacteroides, and Shigella increased. Discussion This study showed that the richness of the gut microbiota decreased with age in patients with sarcopenia. Furthermore, the relative abundance of different microbiota changed related to age, comorbidity, participation in protein metabolism, and other factors. This study provides new ideas for targeting the gut microbiota for the prevention and treatment of sarcopenia. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=475887, CRD475887.